PROSES PELAPISAN BAJA DENGAN METODE SEMBURAN KAWAT LAS OKSI-ASITILEN - Muhammad Ridlwan (Faculty of Industrial Technology Universitas Islam Indonesia, 2006)
Wire flame spray process is one of metal coating technique. The flame spray process is basically the spraying of molten metal onto a surface to provide a coating. Material in wire form is melted in a flame (oxy-acetylene flame most common) and atomized using compressed air to form a fine spray. When the spray contacts the prepared surface of a substrate material, the fine molten droplets rapidly solidify forming a coating. In this research, commercial steel wire (Fe-C), which has 1.25 mm in diameter, was used as raw material. The wire was heated and melted by two oxy-acetylene nozzles and then sprayed onto steel bar surface to form a coating. Vickers hardness testing and optical microscope were used to define the coating characteristic. The result shows that the coating has higher hardness number than the substrate material and the intrusion of carbon was founded in the coating microstucture.Keywords: coating process, wire flame spray, oxy-acetylene